Recognizing the effectiveness of the diode laser 850nm on stimulate the proliferation and viability of mice mesenchymal stem cells derived from bone marrow and adipose tissue - Z. AL-Timimi; F. Mustafa (Iraqi Journal of Veterinary Sciences, 2019)
Low Power Laser Irradiation therapy raises the levels of proliferation for the variety of cells. Although despite very little is recognized about its effect on the proliferation levels and possible nuclear morphological changes of mice mesenchymal stem cells, which derived from bone marrow and adipose tissue. This study examined the effects of the different fluence of 1, 2, 3 and 4 j/cm² with different dose durations on promoting proliferation, viability and possible nuclear morphological changes of mice mesenchymal stem cells. The growth curves have been used to analyse the proliferation of all the applications. Fluorescent stain (DAPI) (4’-6-diamidino-2-phenylindole) staining used to check the nuclear alterations at 72 hours, while the trypan blue assay used to test the cell viability. Mesenchymal stem cells that derived from bone marrow responded to LPLI in a dose-dependent manner. The higher cell growth determined once the cells irradiated with a fluence of 4 j/cm², especially after 24 hours (P<0. 01). Whereas adipose tissue-derived stem cells responded better to a fluence of 2 j/cm² after 48 hours (P<0. 05). There was no significant change in nuclear alterations and in cell viability detected in the studied groups. LPLI permits a significant increase in the proliferation of stem cells, without causing nuclear alterations, therefore, increasing the number of differentiating cells for tissue engineering, regenerative, and healing processes.